Minecraft. Volume 2 - Monster, Sfé R. (Dark Horse Books, 2020)
Evan is struggling with a bully. He tries to keep it quiet from his friends, but when they encounter a similar situation in the EverRealm, Evan finds himself revealing the truth. When they are attacked by pirates and an even bigger threat, Evan and his friends must work together to face a new enemy.